Remote learning in the opinion of academic youth - Jastrzębska, Joanna (Physical education, sport and olympism from a pedagogical perspective, 2023)
The purpose of the fragment of the results of our own research presented in the article was to find out the opinions of students of selected specialties of the pedagogy faculty of the Faculty of Education Sciences of the University of Łódź on remote education and to determine any differences between the respondents studying early childhood education and physical and health culture.The diagnostic survey method and survey technique were used to conduct the study. A specially constructed survey questionnaire was filled out by 127 students, including 96 women and 31 men, 61 studying physical and health culture specialties and 66 female students of early childhood education. The results of the study were statistically analyzed by assessing the statistical significance of the differences using the chi-square test. The results show that more than half of the respondents have a negative attitude toward distance education, including more physical and health culture students than female early childhood pedagogy students. According to the students, the system limits contact with peers and instructors, does not encourage further work, and is unable to clarify nagging problems. The main advantages of e-learning were found to be cost-effectiveness, time-saving, and the possibility of learning anywhere at any time.